A novel resistance gene for bacterial blight in rice, Xa43(t) identified by GWAS, confirmed by QTL mapping using a bi-parental population - Kim, Suk-Man; Reinke, Russell F. (Public Library of Science, 2019)
Bacterial blight (BB) caused by the Xanthomonas oryzae pv. oryzae (Xoo) pathogen is a significant disease in most rice cultivation areas. The disease is estimated to cause annual rice production losses of 20–30 percent throughout rice-growing countries in Asia. The discovery and deployment of durable resistance genes for BB is an effective and sustainable means of mitigating production losses. In this study QTL analysis and fine mapping were performed using an F2 and a BC2F2 population derived from a cross with a new R-donor having broad spectrum resistance to Korean BB races. The QTL qBB11 was identified by composite interval mapping and explained 31.25% of the phenotypic variation (R2) with LOD values of 43.44 harboring two SNP markers. The single major R-gene was designated Xa43 (t). Through dissection of the target region we were able to narrow the region to within 27.83–27.95 Mbp, a physical interval of about 119-kb designated by the two flanking markers IBb27os11_14 and S_BB11.ssr_9. Of nine ORFs in the target region two ORFs revealed significantly different expression levels of the candidate genes. From these results we developed a marker specific to this R-gene, which will have utility for future BB resistance breeding and/or R-gene pyramiding using marker assisted selection. Further characterization of the R-gene would be helpful to enhance understanding of mechanisms of BB resistance in rice.